Long-term oncologic outcomes and prognostic factors related to recurrences in pathologic Stage I/II early oral tongue cancer - Kwak, Jin Hye; Ji, Yong Bae; Song, Chang Myeon; Lee, Young-Jun; Park, Hae Jin; Tae, Kyung (Frontiers in Surgery, 2025)
ObjectivesThis study aimed to evaluate long-term treatment outcomes and identify prognostic factors affecting survival and recurrence of Stage I/II tongue cancer, with a specific emphasis on early recurrence.MethodsWe retrospectively studied 65 patients with pathologic Stage I/II oral tongue squamous cell carcinoma (OTSCC), who underwent definitive surgical treatment, with or without postoperative adjuvant therapy, from 1997 to 2022.ResultsThirteen (20%) cases experienced recurrence. The 2-, 5-, and 10-year overall survival rates were 91.7%, 88.0%, and 81.5%, respectively. Univariate Cox analyses showed that recurrence and overall survival were significantly associated with Stage II, depth of invasion (DOI) > 5 mm, lymphovascular invasion (LVI), and perineural invasion (PNI). Multivariate Cox analysis identified LVI as an independent predictor of recurrence and PNI as an independent predictor of survival. Second primary tumors in the head and neck region occurred in 10.8%, and both recurrence and second primary tumors significantly decreased survival in univariate and multivariate analyses. Early recurrence (within 6 months post-surgery) occurred in 3 patients (23.1% of recurrences), with no significant predictors identified by Cox analysis.ConclusionsRecurrence and survival of early OTSCC are associated with Stage II disease, high DOI, PNI, and LVI in univariate analysis. Also, in patients with early OTSCC, prevention and proper treatment of second primary tumors and recurrence are crucial for improving overall survival.